Bed properties and three-dimensional topography from radar at Rutford Ice Stream, West Antarctica - REBECCA SCHLEGEL (2022)
Outlet glaciers and ice streams of the Antarctic Ice Sheet provide dis-charge pathways, transporting >90% of the continents ice into the oceans. Elongated landforms beneath fast ﬂowing ice streams form as a result of ice-bed interactions. Understanding their link to ice ﬂow dynamics will better inform subglacial processes and allow these processes to be correctly implemented in predictive numerical ﬂow models, thus improving predictions of future contributions to sea level rise. In this thesis, a section of the bed of Rutford Ice Stream (West Antarctica), containing numerous elongated subglacial landforms, was analysed using a suite of 2D and 3D radar data with repeat surveys. Bed properties vary spatially over a 100 m scale and imply the pat-tern of inferred basal motion in this area is more complex, and basal sliding dominated areas are more extensive, than previously assumed. Local erosion rates are high (1 m/a), indicating a mobile bed, whereas most of the bed shows no temporal change, implying stability of the basal environment. Observations of landforms shortening, and previ-ous observations of landforms extending, highlight that landforms are a non-static part of the bed. Isolated landforms appear to consist of a more rigid sediment at their upstream end with softer sediment down-stream. Some landforms contain a water body (up to 10 km length) along their crest. 3D processed data reveal a so far unseen moat (de-pression) around one landform. Dimensions of the upstream part of the moat are comparable to dimensions of the upstream end of the landform (<50 m height, <300 m width). Observations suggest land-forms are depositional features, while the moat was likely eroded. The radar and other data analysed provide detailed landform and moat ar-chitecture, at a resolution comparable to digital elevation models of deglaciated terrain, and together with interpreted properties give a solid basis for testing existing landform formation theories.